Virtual Mirrors and Distorted Reflections: Investigating Social Media’s Influence on Body Image and Eating Behaviour of Young Adults in Mumbai - Anilkumar, Ashwathi (Asian Journal of Media and Communication, 2024)
In the vortex of virtual mirrors, young adults find themselves at the epicentre of body ideals and dietary trends. This study examines the relationship between social media, body image and eating behaviours of urban young adults in Mumbai. It explores usage patterns, analyses the impact of body-centric content on perceptions and behaviours, and assesses the youth’s awareness of social media’s potential influence on eating disorders and mental health. The primary empirical data were collected through an online survey, utilizing a semi-structured questionnaire from 360 respondents in Mumbai who were selected based on specific criteria, i.e. aged 15 – 29 years and regularly use social media. This study found that social media has become the foreground of body image ideals, weight loss endeavours, and dieting trends which are not necessarily fact-based. The practice of photo editing, dietary changes, and the act of comparing oneself to others on social media are prevalent among respondents. These findings provide insights into the complex role of social media in young adults’ lives, underscoring the need for targeted interventions and fostering responsible online behaviours through media literacy.